Interferometry concepts. Issue 69 (10th September 2015) - Millour, F.
Abstract : This paper serves as an introduction to the current book. It provides the basic notions of long-baseline optical/infrared interferometry prior to reading all the subsequent chapters, and is not an extended introduction to the field.